Do mutations in DNMT3A/3B affect global DNA hypomethylation among benzene‐exposed workers in Southeast China?: Effects of mutations in DNMT3A/3B on global DNA hypomethylation. (25th September 2017) - Zhang, Guang‐hui; Lu, Ye; Ji, Bu‐qiang; Ren, Jing‐chao; Sun, Pin; Ding, Shibin; Liao, Xiaoling; Liao, Kaiju; Liu, Jinyi; cao, Jia; Lan, Qing; Rothman, Nathaniel; et al.
Abstract : Global DNA hypomethylation is commonly observed in benzene‐exposed workers, but the underlying mechanisms remain unclear. We sought to discover the relationships among reduced white blood cell (WBC) counts, micronuclear (MN) frequency, and global DNA methylation to determine whether there were associations with mutations in DNMT3A/3B. Therefore, we recruited 410 shoe factory workers and 102 controls from Wenzhou in Zhenjiang Province. A Methylated DNA Quantification Kit was used to quantify global DNA methylation, and single nucleotide polymorphisms (SNPs) in DNMT3A (rs36012910, rs1550117, and R882) and DNMT3B (rs1569686, rs2424909, and rs2424913) were identified using the restriction fragment length polymorphism method. A multilinear regression analysis demonstrated that the benzene‐exposed workers experienced significant global DNA hypomethylation compared with the controls (β = −0.51, 95% CI: −0.69 to −0.32, P  < 0.001). The DNMT3A R882 mutant allele (R882H and R882C) (β = −0.25, 95% CI: −0.54 to 0.04, P  = 0.094) and the DNMT3B rs2424909 GG allele (β = −0.37, 95% CI: −0.70 to −0.03, P  = 0.031) were significantly associated with global DNA hypomethylation compared with the wild‐type genotype after adjusting for confounding factors. Furthermore, the MN frequency in the R882 mutant allele (R882H and R882C) (FR = 1.18, 95% CI: 0.99 to 1.40, P  = 0.054) was higher than that of the wild‐type. The results imply that hypomethylation occurs due to benzene exposure and that mutations in DNMTs are significantly associated with global DNA methylation, which might have influenced the induction of MN following exposure to benzene. Environ. Mol. Mutagen. 58:678–687, 2017. © 2017 Wiley Periodicals, Inc.